The neurocognitive and functional profile of schizophrenia in a genetically homogenous European sample. (October 2021) - da Motta, Carolina; Pato, Michele T.; Barreto Carvalho, Célia; Castilho, Paula
Highlights: We explore several neurocognitive and functional impairments of schizophrenia. 3 samples at different risk levels were compared. Memory, executive function, social and complex cognition were significantly impaired. Functional outcomes were severely impaired in affected and at-risk individuals. Implications to intervention strategies with patients and caretakers are discussed. Abstract: Schizophrenia is a complex heritable brain disorder that entails significant social, neurocognitive, and functional deficits, and significant psychosocial challenges to affected and unaffected family members. In this cross-sectional study, we explore impairments in specific neurocognitive and social cognition processes in patients affected with schizophrenia, unaffected relatives, and in controls to provide a characterization of a genetically homogenous European sample from an endophenotypic and functional standpoint. A sample of 38 affected patients, 28 first-degree relatives, and 97 controls performed a series of computerized and skills-based assessments. Samples were compared across several neurocognitive, social, and functional domains. Significant impairments in episodic memory, executive function, social cognition, complex cognition, sensorimotor domains were found in patients and first-degree relatives. Findings also showed increased processing speed in memory and other complex cognitive processes relevant to autonomous living. A discriminant function analysis yielded 2 functions allowing 79% of correct group classifications based on social cognition and functional skills, neurocognition, and age. The study highlights the importance of resourcing to wide-ranging assessment methodologies, of developing research efforts to further understand the decline of social and neurocognitive processes, and the need for designing more targeted intervention strategies to be implemented both with affected patients and families.